IMPLEMENTATION OF CONSTRUCTIVE THEORY IN PAI LEARNING DESIGN IN SUMBAWA BESAR 2 STATE HIGH SCHOOL - Muhammad Junaidi; Saparudin Saparudin; Emawati Emawati (Conciencia, 2022)
Various efforts have been made to improve the quality of education. As well as to prove that the meaningfulness of PAI learning in the learning process is very closely related to the theory used. One of them is by implementing constructivist theory in learning. As was done at SMA Negeri 2 Sumbawa Besar in the PAI learning process. The purpose of this study was to analyze the implementation of constructivist learning theory in PAI learning design, and to find out the meaningful implications of constructivist learning theory in the PAI learning process at SMA Negeri 2 Sumbawa Besar. This study uses a field research method that is descriptive qualitative, with the research location at SMA Negeri 2 Sumbawa Besar. Data collection was carried out by observation, interview and documentation methods. The object of research in this research is the implementation of constructivist theory in Islamic Islamic education learning design, while the research subjects are 4 Islamic Islamic education subject teachers and students of class X and XI. And to analyze the data obtained from the research results, the author uses data analysis techniques consisting of of the three flow of activities namely data reduction, data presentation and verification or drawing conclusions. From the results of the analysis it was concluded that, the planning of constructivist theory in the design of PAI learning has been realized in the PAI learning process that has been carried out even though there are still obstacles when the learning process takes place. In which there are already 4 learning steps with a constructivist approach, namely the apperception stage, the exploration stage, the discussion stage and concept explanation. Evaluation of learning by the teacher still tends to prioritize the assessment of results in the cognitive domain of students through doing exercises that have been prepared by the teacher.